Indirect selection of maize genotypes based on associations between root agronomic and anatomical characters - Nascimento-Junior, Ivanildo; Moro, Gustavo V. [UNESP]; Moro, Fabiola V. [UNESP] (Inst Investigaciones Agropecuarias, 2018)
Indirect selection based on highly correlated characters is a common strategy in genetic improvement to quickly and accurately identify genotypes with good agronomic characteristics. The objective of this research study was to quantify existing associations between root agronomic and anatomical characters in maize (Zea mays L.) populations for possible indirect selection. The following agronomic characters were considered: Plant height, ear insertion height, relative ear position, plant lodging, plant breakage, and grain productivity. Measured anatomical characters included total root area, central cylinder area, epidermis thickness, exodermis thickness, endodermis thickness, cortical parenchyma thickness, number of metaxylem vessels, phloem area, cortex thickness, and metaxylem area. The genotypic correlation analysis showed significant associations at the 1% probability level between the following anatomical and agronomic characters: Endodermis thickness and plant height, exodermis thickness and plant breakage, and exodermis thickness and grain productivity. The canonical analysis of variance showed significant effects by the chi-square test for three of the five canonical pairs. The first canonical pair showed a positive relationship between plant height and total root area (4.142) and a negative relationship with the central cylinder area (-4.080), indicating that genotypes with greater total root area and lower central cylinder area can give rise to larger plants. These results indicated the possibility of an indirect selection of taller or shorter plants in the earlier growth stages using anatomical root characters.
Keywords: Canonical correlation; correlation between characters; multivariate analysis; Zea mays